Emulsion polymerization of styrene and vinyl acetate with cationic surfactant - Erkal, Durdane; Senkal, B. Filiz; Sarac, Ayfer (WILEY-V C H VERLAG GMBH, 2007)
In this study, the emulsion homopolymerization system containing vinyl acetate and styrene, potassium persulfate, and a new cationic surfactant was studied in the classical glass emulsion polymerization reactor. The effects of new polymeric emulsifier on the physicochemical properties of obtained vinyl acetate and styrene latex properties were investigated depending on surfactant percentage in homopolymerizations.
Keywords: emulsion polymerization; lattices; stabilization; surfactants; N-BUTYL ACRYLATE; METHYL-METHACRYLATE; MIXED EMULSIFIERS; LATEX-PARTICLES; COPOLYMERIZATION; KINETICS; Polymer Science